Analysis Of Environmental, Social, And Governance Performance In Mineral And Coal Mining Companies - Fajar Kurniawan; Juniati Gunawan (Cita konsultindo, 2024)
This research aims to analyse Environmental, Social and Governance (ESG) performance, which includes: 1) analysing the performance of ESG implementation through disclosures in sustainability reports, 2) analysing challenges in implementing ESG, and 3) analysing strategies in facing challenges in implementing ESG. This research uses qualitative methods in analysing ESG performance through disclosure based on the International Council on Mining & Metal (ICMM) Principles framework, challenges faced in implementing and improving ESG performance, as well as strategies implemented to improve ESG performance. The subjects of this research are coal mining companies (PT A and PT B) and mineral mining companies (PT C and PT D), which were selected using purposive sampling, considering the largest capitalisation in the mineral mining and coal mining sub-sector companies, which are listed on the Indonesia Stock Exchange (BEI), and represent mineral and coal mining companies, both private and state-owned. The research results show that in disclosing the performance of ICMM principles in the sustainability report from 2018 to 2022, it is known that the highest disclosure is the performance indicator on Principle 5 - Occupational Health and Safety (75%) and the lowest is the performance indicator on Principle 3 - Human Rights (30%). The challenge in implementing ESG is that several international standards and guidelines for corporate social management have not been adopted. This research also found that the existence of top management support, the existence of clear policies and roadmaps for implementing ESG, a clear organizational structure, and the preparation of competent human resources are strategies for improving ESG performance.